The flash effect in electronic conductors: The case of amorphous carbon fibers. (1st April 2020) - Ingraci Neto, Rubens Roberto; Raj, Rishi
Abstract: Fibers of amorphous carbon are deployed as a model system to explore the incidence of flash in electronic conductors. The onset of flash is confirmed by a non-linear rise in conductivity and intense electroluminescence. The electroluminescence spectra are quite different from those seen in oxides. Flash causes a significant transformation of the amorphous carbon into graphite. However, flash also leads to embrittlement of the fibers presumably by the scission of covalent bonds. The fibers were heated with electrical current without using a furnace. The maximum temperature remained just below the melting point of platinum, the metal used for the electrodes. Graphical abstract: Current induced flash in carbon fibers signaled by elecctroluminescence and rise in conductivity. Image, graphical abstract